Trends in incidence and mortality of esophageal cancer in China 1990−2019: A joinpoint and age-period-cohort analysis - Li, Fajun; Li, Haifeng; Su, Xin; Liang, Hongsen; Wei, Li; Shi, Donglei; Zhang, Junhang; Wang, Zhaojun (Frontiers in Oncology, 2022)
Background: The incidence and mortality trends of esophageal cancer (EC) remain unknown in China. This study aimed to describe the trend in incidence and mortality of EC in China. Methods: We extracted age-standardized rates and numbers of EC in China for 1990−2019 from the Global Burden of Disease study 2019. The age-standardized incidence rate (ASIR) and age-standardized mortality rate (ASMR) were calculated to describe the trends, while the annual percentage of change and the average annual percent change (AAPC) were analyzed by the joinpoint regression analysis. The incidence and mortality data were analyzed via age-period-cohort model analysis. Results: The ASIR and ASMR decreased slightly before 1999, then increased from 1999 to 2004, and decreased again thereafter, with overall AAPC values of −2.5 (−2.8, −2.1) for females and -0.9 (−1.1, −0.8) for males regarding incidence, with overall AAPC values of −3.1 (−3.3, −2.9) for females and −1.2 (−1.3, −1.1) for males regarding mortality. As a whole, the relative risk (RR) of EC increased with age in both females and males regarding incidence and mortality, except for the 80–84-year-old age group in females and the 85–89-year-old age group in males, where they began to decrease. The RR of EC increased with age in females and males, except for the 85–89-year-old age group in males. The time period showed a trend of first rising and then decreasing, and the group studied in 2015 had lower scores than the group studied in 1990 in females regarding both incidence and mortality, whereas males showed a significant upward trend in both incidence and mortality. The cohort effect showed an overall downward trend. Conclusions: The overall incidence and mortality of EC in China shows an increased and then decreased trend from 1990 to 2019. The AAPC decreased in incidence and mortality from 1990 to 2019. The RR of incidence and mortality of EC in China is greatly affected by age and time period and should be paid more attention to．